Aspectos da história de vida de Guadua tagoara (Nees) Kunth (Poaceae:Bambuseae) na Serra dos Órgãos, RJ - Alves, Gilberto Terra Ribeiro (Universidade Federal de São Carlos, 2007)
Guadua tagoara (Nees) Kunth is a large sized bamboo native of the Brazilian Atlantic Rain Forest, with a semi-scandent habitat, pachymorphic rhizome and thorns for fixation on trees. Nowadays this bamboo is considered an invasive species in secondary forests, where its populations are supposedly in expansion. The general objective of this study, developed in Parque Nacional da Serra dos Órgãos (PARNASO), RJ, was to investigate the life history of G. tagoara from two perspectives: (a) to know the ecological basis of its supposed invasive potential and (b) to discuss it in the context of theoretical ecology and evolution of mast seeding plants. This dissertation was based primarily on three moments of the G. tagoara life cycle, studied in the scales of clump, genet and ramet. The investigated aspects of its life history were: mast seeding followed by parental death (monocarpy), regeneration from seed, synchrony and reproductive interval, development, morphological plasticity and intra and infra-specific diversity. At least at PARNASO, the life cycle of G. tagoara is strictly monocarpic, its regeneration from seeds occurred mainly in the interior of the senescent clumps. The majority of reproductive events were concentrated in 2004, suggesting a pattern known as flowering distribution for this region. The spatial gregarism of G. tagoara seems to be associated to the intra-clump reproductive synchrony, and the selective advantage of monocarpy seems to be the creation of regeneration sites for the following cohort. The same seems to be valid for other monocarpic species of Guadua with a tendency for gregarism. It was not possible to establish a reproductive interval for G. tagoara, but four possible flowering patterns were proposed for its life history. Although the adult genets have long spacers (necks), the rhizomes in the 2004 and 2006 cohorts did not present this character. Culm ramification occurred before rhizome ramification, and the thorns appeared just in the second year of the young genets. These cohorts (2004 and 2005) differed among them in structural characters, except in the number of living culms per genet, and presented characteristics here considered to be adaptations for the regeneration inside the clumps or other kinds of gaps. The morphological plasticity presented by the different patterns of ramification, by the reiterative growth and by the deviance from obstacles during elongation was observed in the culms of adult genets. The reiterative growth was also seen in the 2004 and 2005 cohorts, as well as articulated culms and the presence of invertebrates in their interior, including the internodes filled with water. Climatic seasonality doesn t restrict the growth of G. tagoara, but it is potentialized in the rainy season. Adult genets of this bamboo seem to grow during the whole year in PARNASO. Morphological plasticity observed in their culms can be considered a foraging behavior searching for light and space in the canopy. G. tagoara also has a large opportunistic growing behavior, expressed in ramets and genets, and can be considered a structural parasite of trees. Morphological elasticity, potential for clonal growth and integration of phalanx and guerilla strategies seem to be key aspects of its life history and its expansion and dominance in secondary forests. The results of this study support the hypothesis that the expansion of G. tagoara in secondary forests is facilitated by activities altering the structure of the forest. I suggest that the selfperpetuating disturbance cycle proposed to explain the formation and expansion of forests dominated by Guadua spp. in the Amazon forest must also act in the G. tagoara dominated forests, but in this latter case the anthropogenic activities seem to be very important for the origin and expansion of dominance. Some possible causes of its intra and infraspecific diversity of G. tagoara were discussed, based on the knowledge acquired about its life history, as well as some possible relations between its life cycle and the forest dynamics. The need and viability of the management of its populations were also discussed.
Keywords: Ecologia; História de vida; Ecologia populacional; Mata Atlântica; Bambu; Crescimento clonal; Frutificação em massa; Monocarpia; Plasticidade morfológica; Bamboo; Clonal growth; Mast seeding; Monocarpy; Morphological plasticity; CIENCIAS BIOLOGICAS::ECOLOGIA